Characterizing non-box trailer activity and aerodynamic devices for greenhouse gas emissions reductions. (April 2021) - Ventura, Luciana M.B.; (Jade) Jiang, Yu; Boriboonsomsin, Kanok; Scora, George; Johnson, Kent; Collier, Sonya; Yoon, Seungju; Durbin, Thomas D.
Highlights: This study evaluated the benefits of applying aerodynamic devices to non-box trailers. Registration database and activity survey were used to estimate fuel economy benefits. Survey data showed non-box trailers often accumulated more than 50, 000 miles/year. Benefits estimated at 47 million diesel gallons and U.S.$118 million for non-box trailers in U.S. Abstract: Add-on aerodynamic devices (cab-roof fairings, side extenders, side skirts, boat-tails and others) for heavy-duty trailers and tractors provide the potential of fuel savings, cost savings, and the reduction of greenhouse gas (GHG) emissions. The goal of this work was to evaluate potential for aerodynamic devices to provide GHG emission reductions for four trailer types: flatbed, tanker, curtainside, and container chassis. This work included an analysis of a United States (U.S.) national trailer registration database with 253, 191 total trailers and a trailer activity survey of 51 fleets. Flatbed, container chassis, and tanker trailers were relatively extensively used, with 48% and 64% of fleets indicating annual vehicle miles traveled (VMT) per trailer of greater than 50, 000 and 25, 000 miles, respectively. Annual savings based on a 50% and 100% market penetration for the registration database in the U.S. were estimated to be approximately 37.0 to 74.1 million gallons diesel, and $92.6 to $185.1 million in fuel (~U.S.$731 per tractor-trailer), and ~0.38 to 0.76 million metric tons (MMT) CO2eq .